Architecture Design Development of e-Learning for Primary School Learning in Madiun City - Mumtahana, Hani Atun; Pamungkas, Ridho (Universitas Nusantara PGRI Kediri, 2022)
Learning quality can be improved by utilizing technology and digital media in teaching and learning. Based on a survey conducted in 2021 at 33 elementary schools in Madiun City, most teachers still use WhatsApp Group media in delivering material. However, schools with good technological facilities can better understand technology for teachers and students. This research is downstream from previous research that recommended the development of LMS-based e-learning in elementary schools in Madiun City. The importance of good management in documenting the teaching and learning process can be used as monitoring and evaluation material to improve the quality of learning. Data collection in this study was carried out by direct observation at SDN 01 and SDN 03 Manisrejo Madiun City, as well as surveys conducted at 33 elementary schools in the Madiun City Education Office. The results of this research are internal and external condition analysis, business process analysis, Data, and Information architecture design, application architecture design, technology architecture design, and people architecture design which can be used as Pecel-AE application development framework documents.